Tetrahymena as a Unicellular Model Eukaryote: Genetic and Genomic Tools. Issue 2 (1st June 2016) - Ruehle, Marisa D; Orias, Eduardo; Pearson, Chad G
Abstract: Tetrahymena thermophila is a ciliate model organism whose study has led to important discoveries and insights into both conserved and divergent biological processes. In this review, we describe the tools for the use of Tetrahymena as a model eukaryote, including an overview of its life cycle, orientation to its evolutionary roots, and methodological approaches to forward and reverse genetics. Recent genomic tools have expanded Tetrahymena 's utility as a genetic model system. With the unique advantages that Tetrahymena provide, we argue that it will continue to be a model organism of choice.